UPAYA GURU PENDIDIKAN AGAMA BUDDHA MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI SD NEGERI 1 KALIMANGGIS KECAMATAN KALORAN, KABUPATEN TEMANGGUNG - Hariyanto; Walyono; Lili Andriani (Jurnal Pendidikan, Sains Sosial, dan Agama, 2021)
The aims of this study are: to describe the efforts of Buddhist education teacher to improve student’s learning outcomes and to find out how teacher evaluate student learning outcomes in online learning during the covid-19 pandemic at Kalimanggis Elementary School state 1, Kaloran district, Temanggung regency. This study used descriptive qualitative research methods. The methods of data collection were through observation, interviews and documentation. This research was conducted at Kalimanggis Elementary School state 1, Kaloran district, Temanggung regency. The subjects of this study were Buddhist education teachers and students Kalimanggis Elementary School state 1.The results of this study showed that the teacher has succeeded in improving students learning outcomes. Efforts made by teachers to improve student learning outcomes are: improving the quality and creativity in the learning process, increasing students's motivation and interest in online learning, teacher also applied appropriate learning strategies and methods, teacher evaluated learning, collaborate with parents, and maximizing the use of learning media as a support to deliver learning material so that it is easily understood by students. As a result, that maximum learning outcomes are achieved. Keywords: Covid-19, Learning Outcomes, Online Learning, Teacher Efforts.